Análisis de algoritmos criptográficos para la protección de datos del sistema informático del Cuerpo de Bomberos de la Ciudad de Guaranda, año 2023. - Guamán Manobanda, Micaela Jasmin (2023)
Nowadays, data protection is essential to ensure the security of information in computer systems. For this reason, it is important to know the main cryptographic algorithms used to protect data and to understand their weaknesses and strengths in different types of computer attacks. Among the most commonly used cryptographic algorithms are AES 256, DES, SHA 256, ECC, RSA, Blowfish and DSA. It has been pointed out that each algorithm has different characteristics in terms of its functions, security, speed and key size, making them more or less suitable for different applications and contexts. Therefore, in the overall analysis, it has been evidenced that AES 256 is one of the most secure algorithms, being widely used in privacy protection and data security, while DES is less secure but its speed is moderate. ECC and RSA are public key cryptography algorithms, Blowfish and DSA are symmetric key algorithms; SHA 256 is a standard with a high level of security. According to the analysis, the use of the algorithm in the Guaranda Fire Department system would be recommended. Determining that in the development of the research the most appropriate algorithm is AES 256, defining that it is more secure and efficient compared to other algorithms, in the encryption and decryption of keys. By defining cryptographic algorithms, it improves the security of a system, preventing its data from being breached. Keywords: Cryptography | computer security | cryptographic algorithms | AES 256.